KONFLIK AMBON: KAJIAN TERHADAP BEBERAPA AKAR PERMASALAHAN DAN SOLUSINYA - Debora Sanur Lindawaty (Sekretariat Jenderal DPR RI, 2011)
This paper aims to look at some roots of Ambon recent conflict and its solution. It discusses the background of the communal conflict which emerged in September 2011. It also discusses the role of security in resolving and preventing the re-emergence of new conflict in the future. This analysis uses a qualitative approach and presents explanations descriptive.